Cranberry-derived bioactives for the prevention and treatment of urinary tract infections: antimicrobial mechanisms and global research trends in nutraceutical applications - Jangid, Himanshu; Shidiki, Amrullah; Kumar, Gaurav (Frontiers in Nutrition, 2025)
IntroductionUrinary tract infections (UTIs) are a global health concern, increasingly complicated by antibiotic resistance. Cranberry-derived bioactive compounds, particularly proanthocyanidins (PACs), have emerged as a promising non-antibiotic strategy for UTI prevention. This review examines their efficacy, mechanisms of action, and the evolving research landscape through bibliometric analysis.MethodsA comprehensive literature review was conducted to assess the role of cranberry metabolites in UTI prevention, focusing on anti-adhesive and antimicrobial mechanisms. Additionally, a bibliometric analysis of publications from 1962 to 2024 was performed to evaluate research trends, collaboration networks, and thematic developments.ResultsCranberry metabolites, particularly A-type PACs, flavonoids, and phenolic acids, inhibit Escherichia coli adhesion to urothelial cells, reducing UTI recurrence. Gut microbiota-driven transformation of PACs into bioactive metabolites enhances their efficacy, while cranberry oligosaccharides disrupt biofilm formation in high-risk populations. Bibliometric analysis reveals a surge in research interest post-2000, with increasing global collaborations and a focus on clinical applications.Discussion and conclusionCranberry bioactives demonstrate significant potential in UTI management, yet variations in formulation, dosage, and metabolic bioavailability present challenges. The growing research interest underscores the need for standardized clinical studies to optimize therapeutic efficacy and establish evidence-based guidelines for their use.